Religiusitas Memoderasi Pengaruh Love of Money, Narsisme, Machiavillianisme Terhadap Persepsi Etis Mahasiswa Akuntansi - Retno Hernawati; Agustin Butar-Butar (ManBiz: Journal of Management and Business, 2025)
This study aims to determine (1) the effect of love of money, narcissism, machiavillianism on ethical perceptions of accounting students (2) religiosity influences the relationship of love of money, narcissism, machiavillianism on ethical perceptions of accounting students. The sampling technique used purposive sampling method. The sample is 396 students. Instrument validity was tested using Confirmatory Factor Analysis (CFA) and reliability test using Cronbach's alpha. Data analysis used multiple linear regression analysis techniques and Moderated Regression Analysis (MRA). The results showed that the love of money, narcissism, and machiavillianism had a negative effect on the ethical perceptions of accounting students. Religiosity can influence the relationship of love of money, narcissism to ethical perceptions but religiosity cannot affect the relationship of machiavillianism to ethical perceptions.